ANALISIS RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE) DAN ECONOMIC VALUE ADDED (EVA) UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN (Studi Pada PT. Gudang Garam,Tbk yang Terdaftar di Bursa Efek Indonesia) - Baety, Isnaini Nur; Pratiwi, Ni Made Ida (Jurnal Dinamika Administrasi Bisnis, 2021)
ABSTRACT            Financial performance assessment is an important thing for thr company, because with an assessment of the company’s financial performance can find out its financial condition which can then be used as ann evaluation by the company to be used as a basis for  making decisions, policies or strategies that are right for the company, so that the company can still grow and develop in quality and quantity.  In this study researchesrs used a measure of Return on Asset (ROA), Return on Equity (ROE) and Economic Value Added (EVA), with an industry average asessment standard that is  if the ROA value  > 9%, ROE value > 15% and EVA value > 0 (positive value), then the company can be said to have good financial performance.  This study aims to describe the financial performance  of PT.Gudang Garam,Tbk which is registered in Bursa Efek Indonesia.  The object of this research is the financial statements of PT.Gudang Garam,Tbk.  The result of this study explain that although there are a few deficiencies that occur in 2016-2018 where the company has not been able to produce a value of EVA>0, in 2019 the company has succeeded in increasing the value of EVA to be positive.  Other than that the results of the ROA and ROE values obtained are all ebove the industry stabdard average value, so it can be said that overall the company’s finsncial performance is good. Keywords : Return on Assets, Return on Equity, Economic Value Added, Financial Performance